PENGARUH FAKTOR EKONOMI, SOSIAL DAN DEMOGRAFI TERHADAP KONTRIBUSI PEREMPUAN PADA PENDAPATAN KELUARGA DI SEKTOR INFORMAL KECAMATAN MELAYA, KABUPATEN JEMBRANA - I Gusti Ayu Kartika Candra Sari Dewi; Made Suyana Utama; AAIN Marhaeni (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2016)
The participation of women nowadays is not just demanding equal rights but also their significant role forthe development of Indonesian society. The participation of women involves tradition and transitions roles. Thisstudy aims to analyze; 1) women’s contribution to family incomes in the informal sector 2) the effect of the levelof education, work experience, age, number of dependents and the intensity of adat and religious activities of theoutpouring of the working hours of women in the informal sector. 3) the effect of the level of education, workexperience, age, number of dependents, the intensity of customary and religious activities as well as the women’stime dedication to family income. 4) the role of the outpouring of the working hours of women in mediating the effectof level of education, work experience, age, number of dependents and the intensity of religious and adat activitiesof the contribution of women to family incomes in the informal sector in the District Melaya, Jembrana Regency.The data Sources were primary data obtained through direct interviews to women traders and the secondary datawere obtained from the Central Bureau of Statistics in Jembrana Regency. The data collection method used wasinterviews and questionnaires, with the number of respondents as many as 129 people. The analytical tool used wasdescriptive analysis and path analysis. The results showed the contribution of women was very instrumental in increasing family incomes; women’scontribution to the family income was at an average of 45.53 percent. The level education and the number ofdependents had a significant positive effect on the outpouring of working hours of women in the informal sector.The intensity of adat and religious activities had a significant negative effect on the outpouring of working hours ofwomen in the informal sector. Work experience and age did not have a significant effect on the outpouring of theworking hours of women in the informal sector. The level of education, number of dependents and the outpouringof hours of work had a significant positive effect on women’s contribution to family incomes in the informal sector.The intensity of adat and religious activities had a significant negative effect on women’s contribution to familyincomes in the informal sector. Work experience and age had no significant effect on women’s contribution to thefamily income. Outpouring of working hours mediated the effect of educational level, number of dependents, as wellas adat and religious activities to the contribution of women in the family income. But the outpouring of workinghours did not mediate the effect of work experience and age on women’s contribution to the family income in thedistrict of Melaya, Jembrana Reegency.